Making Trash Cans and Dissemination of Waste Control in Lumbangrejo Village: Pembuatan Tong Sampah dan Sosialisasi Pengendalian Sampah di Desa Lumbangrejo - Damara, Yuniar Sekar; Febriansah, Rizky Eka; Ningtias, Riska Putri Ayu; Macella, Sherina Ariesty; Umami, Nur Reza; Agustine, Rilla (Procedia of Social Sciences and Humanities, 2022)
Awareness and concern for handling waste by the people of Sumberwekas Hamlet, Lumbangrejo Village, Kec. Prigen, Kab. Pasuruan looks still very lacking. This is marked by the habit of burning waste that is still inherent in the community in managing waste. Even though it is clear the impact of the pollution left behind. Especially with the increasing number of waste cases causing concern among the public. This concern can be reduced by raising public awareness of the importance of disposing of waste in its place and sorting waste. The results achieved from this activity are that the community is expected to begin to understand the importance of managing waste and reducing the volume of household waste expenditure and can increase youth participation to encourage healthy living and generate income. This study aims to determine the public's perception of the waste management program, from the program aspects, namely, socialization, providing facilities and infrastructure, as well as sorting, composting, and recycling waste.